Targeting matrix metalloproteases: A promising strategy for herbal medicines to treat rheumatoid arthritis - Li, Ruo-Lan; Duan, Hu-Xinyue; Liang, Qi; Huang, Yong-Liang; Wang, Ling-Yu; Zhang, Qing; Wu, Chun-Jie; Liu, Shu-Qin; Peng, Wei (Frontiers in Immunology, 2022)
As a type of metalloproteinase, matrix metalloproteinases (MMPs) can be divided into collagenase, gelatinase, stromelysins, membrane-type (MT)-MMPs and heterogeneous subgroups according to their structure and function. MMP contents in the human body are strictly regulated, and their synthesis, activation and inhibition processes should be kept in a certain balance; otherwise, this would result in the occurrence of various diseases. Rheumatoid arthritis (RA) is a known immune-mediated systemic inflammatory disease that is affected by a variety of endogenous and exogenous factors. In RA development, MMPs act as important mediators of inflammation and participate in the degradation of extracellular matrix substrates and digestion of fibrillar collagens, leading to the destruction of joint structures. Interestingly, increasing evidence has suggested that herbal medicines have many advantages in RA due to their multitarget properties. In this paper, literature was obtained through electronic databases, including the Web of Science, PubMed, Google Scholar, Springer, and CNKI (Chinese). After classification and analysis, herbal medicines were found to inhibit the inflammatory process of RA by regulating MMPs and protecting joint structures. However, further preclinical and clinical studies are needed to support this view before these herbal medicines can be developed into drugs with actual application to the disease.